Application of 2D MoS 2 Nanoflower for the Removal of Emerging Pollutants from Water - Joshi, Bhavya; Khalil, Ahmed M.E.; Zhang, Shaowei; Memon, Fayyaz A.; Yang, Zhuxian (ACS Engineering Au, 2023)
Two-dimensional (2D) nanomaterial-MoS (molybdenum disulfide) has gained interest among researchers, owing to its exceptional mechanical, biological, and physiochemical properties. This paper reports on the removal of organic dyes and an emerging contaminant, Ciprofloxacin, by a 2D MoS nanoflower as an adsorbent. The material was prepared by a green hydrothermal technique, and its high Brunauer-Emmett-Teller-specific area of 185.541m /g contributed to the removal of 96% rhodamine-B dye and 85% Ciprofloxacin. Various characterizations, such as X-ray diffraction, scanning electron microscopy linked with energy-dispersive spectroscopy, and transmission electron microscopy, revealed the nanoflower structure with good crystallinity. The feasibility and efficacy of 2D MoS nanoflower as a promising adsorbent candidate for the removal of emerging pollutants was confirmed in-depth in batch investigations, such as the effects of adsorption time, MoS dosages, solution pH, and temperature. The adsorption mechanism was further investigated based on thermodynamic calculations, adsorption kinetics, and isotherm modeling. The results confirmed the exothermic nature of the enthalpy-driven adsorption as well as the fast kinetics and physisorption-controlled adsorption process. The recyclability potential of 2D MoS exceeds four regeneration recycles. MoS nanoflower has been shown to be an effective organic pollutant removal adsorbent in water treatment.